The hidden gallery - Wood, Maryrose; Klassen, J. (New York : Balzer + Bray, 2011)
Fifteen-year-old Miss Penelope Lumley, a governess trained at the Swanburne Academy for Poor Bright Females, takes the three Incorrigible Children of Ashton Place to London, England, and learns they are under a curse.
Booklist
Horn Book Guide
Library Media Connection
Bulletin of the Center for Children's Books
8-12.